Analisa Tegangan Jatuh pada Jaringan Distribusi 20 kV PT.PLN Area Rantau Prapat Rayon Aek Kota Batu - Suprianto, Suprianto (JET (Journal of Electrical Technology), 2018)
Electrical voltage is one of the magnitude of electricity that very influential on a power system as well as a determinant factor  inelectrical power system quality. Over voltage, under voltage and voltage stability, they are the main problem in the elecrical voltage problem, this research aims to evaluate the voltage drop in medium voltage distribution system 20 kV in PT.PLN Area Rantau Prapat Rayon Aek Kota Batu this research is expected to be a reference to make improvement the voltage drop and increasing  quality of electrical power service better. This research was conducted on a radial network of primary distribution systems where voltage drop was observed  at three types of buses in the system ie the main buses, the sub ofmain buses and the lateral buses. The data collection is done according to the data that needed  in analyzing the voltage drop with load flow simulation using Electrical Transient Analysis Program software, the result that obtained then validated by comparing the simulation result with the manual calculation according to related formulas and applicable for the calculation of voltage drop, from the simulation results show that the greatest voltage drop when outside of peak load time is 91,52% or in the magnitude of the voltage is 18,303 kV, this means the voltage drop is 8,49%. For the peak load time the greatest voltage drop is 83,9%, or in the voltage magnitude is 16,779 kV, this means the voltage drop of 16,11% exceeds the standard limit for the maximum allowable drop voltage of 10%. This is likely due to the line cableis loaded for power flow at maximum load,  the quality of line cables is bad or the junction of cable  is lax.